2019
DOI: 10.1177/0165551519849518
|View full text |Cite
|
Sign up to set email alerts
|

A case study for block-based linked data generation: Recipes as jigsaw puzzles

Abstract: This article is a proof-of-concept case study to evaluate the functionality of a block metaphor–based linked data generator. In this work, we chose to produce linked data repository of recipes, which provide a medium for people to share their regional and healthy recipes with the masses. However, the same approach can also be adapted easily to other domains. Therefore, the applicability of our approach extends well beyond the food domain that we are considering in this article. As a medium for information shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…ONE ontology was developed for enhancing reporting and communication of nutritional epidemiologic studies and data (Yang et al., ). And an ontology‐based recipe repository that describes cooking terms and activities was developed for facilitating the sharing and searching of recipe data (Öztürk, & Özacar, ).…”
Section: Application Of Text Data In Food‐related Studiesmentioning
confidence: 99%
“…ONE ontology was developed for enhancing reporting and communication of nutritional epidemiologic studies and data (Yang et al., ). And an ontology‐based recipe repository that describes cooking terms and activities was developed for facilitating the sharing and searching of recipe data (Öztürk, & Özacar, ).…”
Section: Application Of Text Data In Food‐related Studiesmentioning
confidence: 99%
“…Faceted IR (FaIR) showcases the formalisation of facets, where the system provides an interface that allows users to interact with facets by selecting concepts under different facets, thereby modifying the retrieved results [48]. Öztürk and Özacar [49] demonstrate an approach to publishing recipe datasets in linked data format, thereby enabling users (non-experts in ontology) to produce recipe-linked data using recipe-based ontology. Ellis and Vasconcelos [50] address the lack of communication between web-designers and users by bringing web-developers and potential web-users into one common platform of understanding, and by organising a hypertext concept through facet analysis, thereby generating a hypertext knowledge base for designers and a knowledge base interface for users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experiments already indicated that users with similar backgrounds achieved higher performance and had a lower perceived mental workload when creating Linked Data mappings [6]. Recently, [7] reported on a block-based approach for instantiating a recipe ontology and an evaluation with an experiment involving 14 participants. Their method consists of designing blocks and mapping their contents to RDF according to their ontology.…”
Section: Related Workmentioning
confidence: 99%
“…This indicates that this metaphor has already been adopted within the community for different purposes. Similar to [7], we adopt this metaphor for the creation of RDF. While the advantage of [7] is the control over the blocks they design for their ontology, the disadvantage is that the approach will not scale well as the ontology evolves, as is the case in our setup.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation